Off-flavor Production of Cihateup Duck Meat at Different Slaughter Ages - Maria Kristina Sinabang; Rukmiasih Rukmiasih; Tuti Suryati; Jonathan Anugrah Lase (Buletin Peternakan, 2021)
This study aims to evaluate the age of off-odor detection to ensure more efficient and economical provision of antioxidants in the production of Cihateup ducks. This study used a Completely Randomized Design (CRD) with 3 different treatments of slaughter age, i.e. 4, 8 and 12 week. Each treatment consisted of 6 replications and each replication consisted of 13 ducks. The results showed that the percentage of fat content at the age of 12 weeks was higher than the age of 4 and 8 week. High fat-containing meat tends to undergo fat oxidation. High levels of Fe at 12 week of slaughter age cause high levels of myoglobin in duck meat. Fe2+ is a catalyst in the process of fat oxidation. the brightness value (L) is inversely proportional to the value a of Cihateup duck meat. The darker brightness of the meat causes the flesh to be redder due to myoglobin level in duck meat. The percentage of polyunsaturated fatty acids (ALTJG) is 4- and 12-week slaughter age lower than 8 week of age. The high levels of MDA at 12 week of slaughter age are due to fat oxidation which causes off-odor. Based on the result, the conclusion is that the high fat content, Fe content, color of Cihateup duck meat at 12 weeks of slaughter age caused the percentage of polyunsaturated fatty acids (ALTJG) to be low due to fat oxidation. Fat oxidation caused high levels of MDA in duck meat (12 weeks of slaughter age) resulting in Off-odors in Cihateup duck meat.